“Nachfolge” by Bonhoeffer: The „Imitatio Christi” of the 20ᵗʰ Century - Fănel ȘUTEU (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Eight decades are precisely marked since Nachfolge, the work of the Lutheran pastor and theologian Dietrich Bonhoeffer (1906–1945), has appeared in the German realm (1937). In 2009, 72 years since that date, the Cluj publisher Peregrinul, published this book in Romanian language. There lies a possibility of the title being translated literally but hermetically, such as: „Succession”, „Emulation”, or „Imitation”. The latter refers to a writing by a medieval monk called Hammerkin, Die Nachfolge Christi (it is about the extremely well known work by Thomas a Kempis, Imitatio Christi). Ligia Taloș – the translator of Bonhoeffer’s work – chose a title accessible to the common Christian reader, probably drawing inspiration from the English version The Cost of Discipleship.